2016
DOI: 10.1098/rsta.2015.0371
|View full text |Cite
|
Sign up to set email alerts
|

Critical factors determining the quantification capability of matrix-assisted laser desorption/ionization– time-of-flight mass spectrometry

Abstract: Quantitative analysis with mass spectrometry (MS) is important but challenging. Matrix-assisted laser desorption/ionization (MALDI) coupled with time-of-flight (TOF) MS offers superior sensitivity, resolution and speed, but such techniques have numerous disadvantages that hinder quantitative analyses. This review summarizes essential obstacles to analyte quantification with MALDI-TOF MS, including the complex ionization mechanism of MALDI, sensitive characteristics of the applied electric fields and the mass-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 107 publications
(126 reference statements)
1
29
0
Order By: Relevance
“…In addition, that range was used to avoid poor co-crystallization with the matrix which can lead to a viscous spot on the MALDI target plate precluding any transfer of energy from the laser to the matrix that enables the desorption of the molecules of interest. 35,36 In addition to optimizing the dilution of the sample, we also tested various solvent mixtures (chloroform, methanol and combinations of those) to solubilize the matrix in order to generate high-quality and reproducible mass spectra. After numerous iterations of optimization, the matrix solvent composed of chloroform and methanol at a ratio 9 to 1 gave mass spectra with a signal-to-noise ratio greater than 10 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, that range was used to avoid poor co-crystallization with the matrix which can lead to a viscous spot on the MALDI target plate precluding any transfer of energy from the laser to the matrix that enables the desorption of the molecules of interest. 35,36 In addition to optimizing the dilution of the sample, we also tested various solvent mixtures (chloroform, methanol and combinations of those) to solubilize the matrix in order to generate high-quality and reproducible mass spectra. After numerous iterations of optimization, the matrix solvent composed of chloroform and methanol at a ratio 9 to 1 gave mass spectra with a signal-to-noise ratio greater than 10 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We found that a sample diluted at a McFarland of 20 to 50 in double‐distilled water was most appropriate for our experiments as it gave spectra with the highest signal‐to‐noise ratio (>10) and mass resolution (>200) (Figure 1). In addition, that range was used to avoid poor co‐crystallization with the matrix which can lead to a viscous spot on the MALDI target plate precluding any transfer of energy from the laser to the matrix that enables the desorption of the molecules of interest 35,36 . In addition to optimizing the dilution of the sample, we also tested various solvent mixtures (chloroform, methanol and combinations of those) to solubilize the matrix in order to generate high‐quality and reproducible mass spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive analyte concentrations will reduce ionization efficacy and thus minimize relative signal increase. Furthermore, quantification by MALDI‐TOF MS might be challenging due to (i) inhomogeneous crystallization and spot‐to‐spot variability causing sweet spots of maximum signal intensity in neighborhood to areas of insufficient analyte concentrations, (ii) less reproducible geometry of matrix spots causing laser shots to miss the targets, (iii) ablation of matrix‐analyte crystals before the total number of preset laser shots has been released, and (iv) ion suppression evoked by non‐analyte molecules present in a complex sample …”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis with MALDI-TOF MS was initially viewed as implausible and inherently irreproducible because the mass spectrum’s signal intensity varies as a function of the sample’s composition, the sample’s morphology, the laser conditions, and sample depletion during continuous laser exposure [ 1 , 2 ]. Inhomogeneous sample deposition is also a crucial obstacle, and leads to poor signal reproducibility (including the so-called “sweet spot” and “coffee-ring” effects) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%